General and efficient route to 3 `-deoxy-3 `-N-, S-, and C-substituted altropyranosyl thymines from 2',3'-O-anhydro-mannopyranosylthymine - Deshpande, Sachin G.; Pathak, Tanmaya (Tetrahedron, 2007)
An efficient route to 1-(2,3-O-anhydro-4,6-O-phenylmethylene–D-mannopyranosyl) thymine from 1,2,4,6-tetra-O-acetyl-3-O-tosyl-beta-D-glucopyranose has been devised. This newly synthesized epoxide is opened up regioselectively at the C-3'-position by N-, S-, and C-nucleophiles to afford a wide range of new 3-deoxy-3'-substituted altropyranosyl thymines. (c) 2006 Published by Elsevier Ltd.

Diastereoselective addition of planar N-heterocycles to vinyl sulfone-modified carbohydrates: a new route to isonucleosides - Sanki, Aditya K.; Bhattacharya, Rahul; Atta, Ananta Kumar; Suresh, Cheravakkattu G.; Pathak, Tanmaya (Tetrahedron, 2008)
Michael-type addition reactions of planar N-heterocycles at the C-2 positions of vinyl sulfone-modified carbohydrates provide an efficient and general route for the carbon-N-heterocycle bond formation. Therefore, the addition pattern of planar heterocycles, such as imidazole, triazole, thymine, and adenine to 3-C-phenyisulfonyl-hex-2-enopyranosides (1 alpha/1 beta) and 3-C-p-toluenesulfonyl-pent-2-enofuranosides (2 alpha/2 beta) was studied for developing a general methodology for the synthesis of new classes of isonucleosides possessing a carbon-N-heterocycle linkage at C-2 positions of furanosyl and pyranosyl sugars. To a great extent, the anomeric configurations of the starting vinyl sulfones play crucial roles in deciding the diastereoselectivity of addition of heterocycles. However, the trityl protected 3-C-p-toluenesulfonyl-hex-2-enopyranosides (33 alpha/33 beta) were judged to be More practical starting materials for desulfortylation and deprotection for the synthesis of a new class of thymine and adenine deoxyisonucleosides. (C) 2008 Elsevier Ltd. All rights reserved.

Studies on the synthesis and unusual behavior of vinyl sulfone-modified hexenopyranosylthymines - Deshpande, Sachin G.; Suresh, Cheravakkattu G.; Pathak, Tanmaya (Carbohydrate Research, 2008)
Although vinyl sulfone-modified- (VSM) pent-2-enofuranosyl nucleosides 2 and hex-2-enopyranosyl glycoside 4 are easily synthesized from the corresponding mesylated sulfones le and 3c, respectively, via an oxidation-mesylation-elimination route, the 3'-C-sulfonyl-hex-2'-enopyranosylthymine 11 is not obtained from 10 and a glycal derivative 12 is formed instead. On the other hand, 3-C-sulfonyl-hex-3'-enopyranosylthymine 20 is easily synthesized from the mesylated sulfone 19. Again unlike the reaction patterns of VSM-pent-T-enofuranosyl nucleosides 2 and hex-2-enopyranosyl glycosides 4 as Michael acceptors, the reactions of nucleophiles with 3'-C-sulfonyl-hex-3'-enopyranosylthymine 20 yielded a rearranged product 21 instead of Michael adducts. (c) 2008 Published by Elsevier Ltd.
Keywords: glycal; hexopyranosyl nucleosides; Michael addition; unsaturated nucleosides; vinyl sulfone-modified nucleosides

Unusual addition of amines to C-2 of vinyl sulfone-modified-beta-D-pent-2-enofuranosyl carbohydrates: synthesis of a new class of beta-anomeric 2-amino-2,3-dideoxy-D-threo-pentofuranosides - Das, Indrajit; Suresh, Cheravakkattu G.; Decout, Jean-Luc; Pathak, Tanmaya (Carbohydrate Research, 2008)
When 3-C-sulfonyl-pent-2-enofuranosides and 3-C-sulfonyl-hex-2-enofuranosides were reacted with primary and secondary amines, only the beta-anomeric methoxy group of the pent-2-enofuranoside did not cause any hindrance to incoming nitrogen nucleophiles. This resulted in the `unusual' addition of amines, in which the diastereoselectivity of the reaction was overwhelmingly in favor of amino sugars of the D-arabino configuration. Selected products were desulfonylated to obtain a new class of beta-anomeric 2-amino-2,3-dideoxy-D-threo-pentofuranosides. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: amino sugars; deoxyaminosugars; desulfonylation with Mg-MeOH-NiBr(2); diastereoselective Michael addition; vinyl sulfone-modified carbohydrates

Experimental and theoretical study on the remarkable influence of protecting groups on the selectivity of addition of amines to vinyl sulfone-modified hex-2-enopyranosides - Bhattacharya, Rahul; Kesharwani, Manoj K.; Manna, Chinmoy; Ganguly, Bishwajit; Suresh, Cheravakattu G.; Pathak, Tanmaya (Journal of Organic Chemistry, 2010)
Although phenylmethylene-protected vinyl sulfone-modified carbohydrate 2 alpha reacts with both primary and secondary amines in Michael fashion to afford aminated products, only primary amines react with the dibenzyl-protected 3 alpha, 6-O-trityl-protected 4 alpha, and unprotected 5 alpha, highlighting for the first time the remarkable influence of protecting, groups on the reaction patterns of vinyl sulfone-modified carbohydrates. The quantum chemical calculations suggest that the Michael addition of amines and proton transfer to vinyl sulfone-modified carbohydrates 2 alpha and 5 alpha are possible via relay process in a concerted mechanism. These calculations reveal that the addition of primary amines to vinyl sulfone-modified carbohydrate is preferential due to the low activation energy barriers, whereas the addition of secondary amines has relatively higher activation energy barriers. The theoretical conclusions are in line with the experimental observations.